"Show me the Numbers": Examining the Dynamics Between Evaluation and Government Performance in Developing Countries. (June 2015) - Hoey, Lesli
Summary: This paper examines the dynamics between monitoring and evaluation (M&E) and government performance in developing countries, where M&E systems are expanding rapidly. Findings in Bolivia suggest that approaches to M&E can lower staff morale, create burdensome paperwork, blind managers to operational problems and emerging innovations, and reinforce self-censorship, contributing to the very problem M&E is intended to solve. Crafted appropriately, M&E can instead become a tool to build practical judgment, increase staff motivation, and improve implementation incrementally. Ultimately, these findings contribute to efforts to design M&E that can support staff working under complex working conditions.